The delusions of crowds : why people go mad in groups - Bernstein, William J. (New York : Atlantic Monthly Press, 2021)
Throughout human history, compelling stories have catalyzed the spread of contagious narratives through susceptible groups-- with enormous, often disastrous consequences. Armed with the latest scientific research that explains the biological, evolutionary, and psychosocial roots of human irrationality. Bernstein tells the stories of dramatic religious and financial manias in western society over the last 500 years. The participants are as colorful as their motivation-- invariably'the desire to improve one's well-being in this life or the next. -- adapted from publisher info
Includes bibliographical references and index.
Keywords: Collective behavior; Delusions; Crowds